Evaluation of Success Factors in Adopting Artificial Intelligence in E-Learning Environment - Ali Alnaqbi, Ali Mohamed; Yassin, Azlina Md (International Journal of Sustainable Construction Engineering and Technology, 2021)
This paper focuses on assessing the critical success factors [CSF] in the adoption of artificial intelligence (AI) technology in E-learning. It is a quantitative assessment study based on the students and teachersâ€™ perceptions of United Arab Emirates the Joint Command and Staff College (JCSC). Data was collected using questionnaire survey where the questionnaire was distributed to a total of 240 JCSC students and teachers of the college. The questionnaire contained 20 CSF in seven group to investigate the level of importance of each CSF in adopting AI and E-learning using 5-points Likert scale. The data was analysed descriptively using SPSS software package. The results of the analysis found that eighteen of twenty CSFs considered in the investigation are reported as high level of importance. The most important CSF is that â€œAI systems able to compute big data for improving teachingâ€ with having the highest mean score of 4.04 in adopting AI technology in E-learning for the UAE military colleges. In term of factorsâ€™ group, the most important group is â€œmaking education more interestingâ€™â€™ with having mean score of 3.98. however, further analysis found that respondents having higher degree picked personalization group while respondent having a lot of teaching experience respondents picked performance monitoring group of factors as the most critical success factors groups. The findings from this study are very helpful in formulating strategies for the promotion of AI advanced technology in the education system and getting its maximum benefits.